The Role Of Independent Commissioners In Overseeing Investment Decisions: A Good Corporate Governance Review In The Extractive Sector - Mutmainna Andi Sudirman; Sukma Aini; Masyadi Masyadi (GENTARA: management and accounting research, 2026)
This study discusses the role of independent commissioners in supervising investment decisions in Indonesian extractive sector companies based on the perspective of Good Corporate Governance (GCG). The study focuses on green capital budgeting, especially reclamation provisions that are required by regulation. Using a systematic literature review method, this study analyzes 31 verified sources, including journal articles, official data, and government regulations published between 2020 and 2026. The results show three main findings. First, agency theory and the triple bottom line framework can be used to explain the importance of independent commissioner supervision. Agency theory explains the risk of information gaps between management and stakeholders, while the triple bottom line highlights the economic, environmental, and social responsibilities of companies. Second, independent commissioners supervise investment decisions through strategic evaluation, monitoring, advisory roles, and accountability reporting. Their effectiveness depends more on active governance involvement than on the number of independent commissioners. Third, reclamation provision adequacy can be used as a new indicator to measure the quality of green capital budgeting in the extractive sector. This study contributes to the Good Corporate Governance literature by linking agency theory, triple bottom line, independent commissioner oversight, and green investment decisions in the Indonesian extractive sector. It also provides a basis for future empirical research on the relationship between reclamation provisions, independent commissioners, and firm value